MPK-1/ERK Regulatory Network Controls the Number of Sperm by Regulating Timing of Sperm-Oocyte Switch in C. elegans Germline - Yoon, Dong Suk (Biochem Biophys Res Commun, 2017)
The precise regulation of germline sexual fate is crucial for animal fertility. In C. elegans, the production of either type of gamete, sperm or oocyte, becomes mutually exclusive beyond the larval stage. Hermaphrodites initially produce sperm and then switch to produce oocytes. This change of fate during germline development is tightly controlled by several regulators. In C. elegans hermaphrodites, FBF-1 and FBF-2 (>95% identical, members of the Pumilio RNA-binding protein family) proteins function redundantly to promote the sperm-oocyte switch. Here, we demonstrate that loss of LIP-1 (dual specificity phosphatase) in fbf-1(ok91) single mutants leads to excess sperm production due to a delayed sperm-oocyte switch. This phenotype was dramatically rescued by depletion of MPK-1 (an ERK homolog). In contrast, loss of LIP-1 in fbf-2(q738) single mutants leads to a premature sperm-oocyte switch and loss of sperm. Notably, fbf-1 fbf-2; lip-1 triple mutants produce excess sperm. These results suggest that the MPK-1/ERK regulatory network, including FBF-1, FBF-2, and LIP-1, controls the number of sperm by regulating the timing of the sperm-oocyte switch in C. elegans.